Why prices don't respond sooner to a prospective sovereign debt crisis - R. Anton Braun; Tomoyuki Nakajima (Federal Reserve Bank of Atlanta, 2011)
We compare the dynamics of inflation and bond yields leading up to a sovereign debt crisis in settings where asset markets are frictionless to other settings with financial frictions. As compared with the case with frictionless asset markets, an asset market structure with financial frictions generates a significant delay in the response of prices to news about a future debt crisis. With complete markets, prices jump in response to news about the possibility of a future debt crisis. However, when short selling of government bonds is restricted, some agents can't act on their beliefs, and prices don't respond to the news. Instead, prices only move in periods immediately prior the crisis.
Keywords: E31; E62; H60; 330; sovereign debt crisis; deflation; fiscal risk; leverage; borrowing constraint